Novel and recurrent FBN1 mutations causing Marfan syndrome in two Chinese families - Li, Dandan; Qiao, Jun; Huang, Dandan; Guo, Ruru; Ji, Jian; Liu, Wei (Frontiers in Medicine, 2022)
Background: To explore the genetic defects of two families with autosomal dominant Marfan syndrome. Methods: Two families with Marfan syndrome were enrolled in this study. The detailed ocular presentations of the patients were recorded. Whole exome sequencing was performed to explore the pathogenic variants and Sanger sequencing was performed to confirm the gene mutations. Segregation analysis among the family members was made and bioinformatics analysis was performed to predict the functional impact of the mutations. Results: The main ocular presentations of the probands were increased axial length and ectopia lentis. Using whole exome sequencing and Sanger sequencing, a novel heterozygous missense mutation (c.5060G>C, p.Cys1687Ser) and a recurrent missense mutation (c.2168A>T, p.Asp723Val) were identified within FBN1, which were co-segregated with the Marfan syndrome phenotype in the families. Evolutionary conservation analysis showed that codons 723 and 1687 were highly conserved among several species. Functional impact predictions made using several online programs suggested that the mutations were pathogenic. Conclusions: We identified a novel and a recurrent missense mutation in FBN1 in two Chinese families with Marfan syndrome using whole exome sequencing, and our bioinformatics analysis indicated that the mutations were disease-causing. Our results expand the mutation spectrum of FBN1 and could help us better understand the genetic defects of the patients with Marfan syndrome.